Formação Econômica do Brasil: Uma análise do discurso em Celso Furtado - NUNES, Gessi Pereira (2023)
This master's thesis aims to analyze the historical-structuralist discourse used by Celso Furtado in his work "The Economic Development of Brazil", identifying the structure adopted by the author and highlighting his influences to substantiate his works, as well as his theoretical approach to development and underdevelopment. The research was carried out through a biographical, bibliographical, and documentary approach, which covers the beginning of Furtado's intellectual trajectory, focusing on the publication of "The Economic Development of Brazil" in 1959, a period that includes his first theoretical reflections and effective public actions, until the year of his death in 2004. This research considers that Celso Furtado's contribution to Brazilian economic historiography is twofold, as his relevance lies in both his intellectual trajectory and his best-known work. His study significantly contributed to understanding the causes and proposals for overcoming underdevelopment in Brazil and Latin America, which highlights his importance and legacy for the Economic Commission for Latin America and the Caribbean (ECLAC). The present study will be conducted through the analysis of the author's intellectual and political trajectory, aiming to approach the main concepts behind Discourse Analysis (DA). Next, a detailed study of Furtado's main work, "The Economic Development of Brazil", will be carried out, highlighting the general characteristics of the Brazilian economy within the author's discourse.